(untitled) - Nakayama, Y. (London, 1999)
Fluid mechanics is often seen as the most difficult core subject encountered by engineering students. The problem stems from the necessity to visualise complex flow patterns and fluid behaviour modelled by high level mathematics. This text overcomes this difficulty by introducing the concepts through everyday examples, before moving on to the more involved mathematics. The various theories of flow have been correlated with real phenomena and, combined with numerous figures and photographs, help the reader place the subject in context. Examples from a broad range of engineering disciplines are included making this textbook suitable for all engineers studying fluid systems as part of their degree.
Cơ học
Keywords: Cơ học chất lỏng,Fluid mechanics